Major hepatectomy in Bismuth types I and II hilar cholangiocarcinoma - Xiong, Junjie; Nunes, Quentin M.; Huang, Wei; Wei, Ailin; Ke, Nengwen; Mai, Gang; Liu, Xubao; Hu, Weiming (The Journal of surgical research, 2015)
Historically, hilar bile duct resection (HBDR) has been regarded as the choice of treatment for Bismuth types I and II hilar cholangiocarcinoma (HCCA). The present study aimed to evaluate the advantages of major liver resection (MLR) in the treatment of patients with Bismuth types I and II HCCA when compared with HBDR. Between January 2005 and September 2012, in total, 52 patients with Bismuth types I and II HCCA who underwent HBDR alone or MLR were included for retrospective analysis. The intraoperative outcomes, postoperative complications, and oncological outcomes including recurrence and overall or disease-free survival rate were compared. The MLR group had significantly higher curative resection rates compared with the HBDR group (95% versus 62.5%, P = 0.021) and lower tumor recurrence (28% versus 63%, P = 0.049), albeit with longer operating time (395.5 ± 112.7 versus 270.9 ± 98.8, P < 0.001), and higher blood transfusion requirements (70% versus 16%, P < 0.001). MLR resulted in significantly higher overall postoperative morbidity (70% versus 34.4%, P = 0.012), compared with HBDR alone. When restricted to R0 resections for all the procedures, MLR significantly increased the overall postoperative survival rate compared with the HBDR group (P = 0.016); the overall survival rate at 1, 3 y was 68.4% and 60.8% for MLR group and 59.6% and 21.9% for HBDR group, respectively. Also, the disease-free survival rate was significantly higher in patients who underwent MLR, as compared with those who underwent HBDR (53.2% versus 0% at 3 y, P = 0.005). Our study has shown that MLR results in higher curative resections, fewer recurrences, and increased postoperative survival rate for Bismuth types I and II HCCA as compared with HBDR alone. However, there is a need for well-designed, multicenter studies to be undertaken to better inform a decision on the standard treatment for Bismuth types I and II HCCA.